Characterization of [3H]-forskolin binding sites in young and adult rat brain cortex: identification of suramin as a competitive inhibitor of [3H]-forskolin binding - Stöhr, Jiří; Novotný, Jiří; Svoboda, Petr (Canadian journal of physiology and pharmacology, 2005)
Little is know about forskolin binding in the rat brain during ontogenetic development. For this paper, we have characterized specific binding sites for [3H]-forskolin in cerebrocortical membranes from young (12-day-old) and adult (90-day-old) rats. High-affinity, as well as super-high-affinity, [3H]-forskolin binding sites were detected in samples from both age groups tested, and the binding parameters of these sites differed significantly. Whereas the number of high-affinity [3H]-forskolin binding sites was higher by about 50% in adult than in young rats, their affinity was markedly (about 4 times) lower. In the presence of AlF4-, the number high-affinity [3H]-forskolin binding sites in samples from young rats rose to the level determined in samples from adult animals, and the number of super-high-affinity sites considerably increased in both age groups. The different characteristics of [3H]-forskolin binding found in cerebrocortical membranes from young and adult rats may be closely related to markedly diminished adenyl cyclase activity in preparations from adult animals. Results of our experiments with suramin indicated that this drug may act as a competitive inhibitor of [3H]-forskolin binding.
Keywords: financování organizované; Animals; Magnesium; Baclofen; hořčík; Rats; Suramin; Rats, Wistar; Cell Membrane; Isoproterenol; Aging; Binding, Competitive; Receptors, Drug; GABA Agonists; guanylylimidodifosfát; baklofen; Colforsin; Adrenergic beta-Agonists; Financing, Organized; Guanylyl Imidodiphosphate; Male; kompetitivní vazba; receptory léků; stárnutí; agonisté adrenergních beta-receptorů; krysa rodu Rattus; GABA agonisté; mozková kůra; Cerebral Cortex; zvířata; mužské pohlaví; suramin; buněčná membrána; kolforsin; isoprenalin; potkani Wistar